2017
DOI: 10.1093/occmed/kqx124
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems among Chinese clinical nurses working in general hospitals

Abstract: The overall prevalence rate of sleep problems among clinical nurses in general hospitals in mainland China was high. Many factors could affect the sleep quality of nurses, although occupational stress facilitates development of sleep problems. Various risk factors associated with sleep problems among nurses should be studied extensively and measures for relieving occupational stress should be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 23 publications
5
31
2
7
Order By: Relevance
“…Nurses working >10 night shifts/month had almost four times greater difficulty in initiating sleep as those working fewer night shifts. Our findings concur with previous studies that high frequency of night shifts per month is related to poor sleep quality (Dong, Zhang, Sun, Sang, & Xu, ; Han, Yuan, Zhang, & Fu, ). Nurses with current or previous night shift work schedules have been reported to complain of insomnia symptoms more than nurses with no night shift work experience (Oyane, Pallesen, Moen, Akerstedt, & Bjorvatn, ).…”
Section: Discussionsupporting
confidence: 93%
“…Nurses working >10 night shifts/month had almost four times greater difficulty in initiating sleep as those working fewer night shifts. Our findings concur with previous studies that high frequency of night shifts per month is related to poor sleep quality (Dong, Zhang, Sun, Sang, & Xu, ; Han, Yuan, Zhang, & Fu, ). Nurses with current or previous night shift work schedules have been reported to complain of insomnia symptoms more than nurses with no night shift work experience (Oyane, Pallesen, Moen, Akerstedt, & Bjorvatn, ).…”
Section: Discussionsupporting
confidence: 93%
“…Nurses have been reported to suffer from poor sleep, especially in large-scale hospitals [21][22][23][24]. In the United States [25], of 540 nurses working in six hospitals, 418 (77.4%) had a poor quality of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other stress parameters not measured in the current study such as effort, reward, overcommitment and support were found to influence the level of depression among workers exposed to high levels of occupational stress whereas the workload (demand) was less important than the other variables [37]. Occupational stress has been reported to facilitate the development of sleep problems [7]. Elger and Sekera [38] indicated that stressful events predicted insomnia, the most prevalent sleep disorder [39].…”
Section: Discussionmentioning
confidence: 52%
“…Occupational strain resulting from exposure to stressors at the workplace can affect an employee's mental and physical health. Depression, the leading cause of disability and the main indication of psychiatric conditions, as well as insomnia, are major psychological disorders reported to be significantly associated with occupational stress [5][6][7]. High levels of occupational stress do not only predict insomnia but also its recurrence [8].…”
Section: Introductionmentioning
confidence: 99%